Expert Apache Cassandra Administration - Alapati, Sam R. (Apress, 2018)
Follow this handbook to build, configure, tune, and secure Apache Cassandra databases. Start with the installation of Cassandra and move on to the creation of a single instance, and then a cluster of Cassandra databases. Cassandra is increasingly a key player in many big data environments, and this book shows you how to use Cassandra with Apache Spark, a popular big data processing framework. Also covered are day-to-day topics of importance such as the backup and recovery of Cassandra databases, using the right compression and compaction strategies, and loading and unloading data. Expert Apache Cassandra Administration provides numerous step-by-step examples starting with the basics of a Cassandra database, and going all the way through backup and recovery, performance optimization, and monitoring and securing the data. The book serves as an authoritative and comprehensive guide to the building and management of simple to complex Cassandra databases. The book: Takes you through building a Cassandra database from installation of the software and creation of a single database, through to complex clusters and data centers Provides numerous examples of actual commands in a real-life Cassandra environment that show how to confidently configure, manage, troubleshoot, and tune Cassandra databases Shows how to use the Cassandra configuration properties to build a highly stable, available, and secure Cassandra database that always operates at peak efficiency What You'll Learn: Install the Cassandra software and create your first database Understand the Cassandra data model, and the internal architecture of a Cassandra database Create your own Cassandra cluster, step-by-step Run a Cassandra cluster on Docker Work with Apache Spark by connecting to a Cassandra database Deploy Cassandra clusters in your data center, or on Amazon EC2 instances Back up and restore mission-critical Cassandra databases Monitor, troubleshoot, and tune production Cassandra databases, and cut your spending on resources such as memory, servers, and storage.